Enabling sustainable built heritage revitalisation from a social and technical perspective: A case study. Issue 11 (5th April 2019) - Ho, Daniel; Hou, Huiying
Abstract : Purpose: This study aims to investigate built heritage revitalisation projects in Hong Kong through a case study. Design/methodology/approach: For this study, a representative built heritage revitalisation project in Hong Kong is selected study revitalisation in practice in Hong Kong. The case study adopts content analysis as the main method of analysis. It involves counting keywords, comparing content, categorising content patterns and interpreting the content of documents. Findings: The findings reveal that in the revitalisation process, there is significant fragmentation in collaboration among government sectors and in conservation documentation and that an effective knowledge sharing mechanism and valid public engagement is needed. A conceptual framework of social network-enabled building information modelling (BIM) platform is proposed to enhance knowledge sharing and cross-sector collaboration. Practical implications: The conceptual framework developed based on the case study is expected to bring practical implications to urban regeneration policies in Hong Kong. Originality/value: This study views built heritage revitalisation practice as different individual projects and provides a social and technical perspective to investigate built heritage revitalisation.